Host-sensitized luminescence of Dy3+ in LuNbO4 under ultraviolet light and low-voltage electron beam excitation: energy transfer and white emission. Issue 35 (23rd August 2017) - Liu, Chunmeng; Zhou, Weijie; Shi, Rui; Lin, Litian; Zhou, Rongfu; Chen, Jun; Li, Zhibing; Liang, Hongbin
Abstract : A single-phase intense white-light-emission is achieved in LuNbO4 :Dy 3+ phosphors. Abstract : A series of LuNbO4 : x Dy 3+ ( x = 0–0.20) phosphors was prepared using a high-temperature solid-state reaction technique. X-ray diffraction (XRD) along with Rietveld refinement, field emission scanning electron microscopy (FE-SEM) observations, diffuse reflectance spectra (DRS), UV-vis photoluminescence (PL), fluorescence decays, PL quantum yields (QYs), and low-voltage cathodoluminescence (CL) were employed to characterize the phosphors. Nonradiative relaxation and host sensitization dramatically influence the LuNbO4 :Dy 3+ luminescence spectra and decay dynamics. It is shown that cross-relaxation arising from electric dipole–dipole interactions between adjacent Dy 3+ ions is the leading mechanism of quenching the Dy 3+ emission. The host sensitization for Dy 3+ emission in LuNbO4 was confirmed and the energy transfer efficiency from the host to Dy 3+ increased with increasing Dy 3+ doping concentration/temperature. Upon excitation with ultraviolet light (261 nm) and a low-voltage electron beam (2 kV, 127 μA cm −2 ), the synthesized LuNbO4 :Dy 3+ phosphors show both the blue broadband emission of the LuNbO4 host and the characteristic emission of Dy 3+ (the dominant one is the 4 F9/2 → 6 H13/2 transition, yellow), and the luminescence colour of the LuNbO4 :Dy 3+ phosphors can be tuned over a large gamut of colours by varying the Dy 3+ doping concentration, and a single-phase intense white-light-emission has been achieved in the LuNbO4 :0.015Dy 3+ phosphor. On the basis of the good UV-vis PL and CL properties, LuNbO4 :Dy 3+ phosphors might be promising for applications in UV light-emitting diodes (UV-LEDs) and field emission displays (FEDs).